Average Error: 0.0 → 0.0
Time: 9.8s
Precision: 64
$A + \alpha \cdot \left(B - A\right)$
$A + \alpha \cdot \left(B - A\right)$
A + \alpha \cdot \left(B - A\right)
A + \alpha \cdot \left(B - A\right)
double f(double A, double alpha, double B) {
double r1725967 = A;
double r1725968 = alpha;
double r1725969 = B;
double r1725970 = r1725969 - r1725967;
double r1725971 = r1725968 * r1725970;
double r1725972 = r1725967 + r1725971;
return r1725972;
}


double f(double A, double alpha, double B) {
double r1725973 = A;
double r1725974 = alpha;
double r1725975 = B;
double r1725976 = r1725975 - r1725973;
double r1725977 = r1725974 * r1725976;
double r1725978 = r1725973 + r1725977;
return r1725978;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$A + \alpha \cdot \left(B - A\right)$
2. Final simplification0.0

$\leadsto A + \alpha \cdot \left(B - A\right)$

# Reproduce

herbie shell --seed 1
(FPCore (A alpha B)
:name "A + (alpha * (B-A))"
:precision binary64
(+ A (* alpha (- B A))))